2013
DOI: 10.4049/jimmunol.1202879
|View full text |Cite
|
Sign up to set email alerts
|

Imprinting of Lymphocytes with Melanoma Antigens Acquired by Trogocytosis Facilitates Identification of Tumor-Reactive T Cells

Abstract: Trogocytosis is a contact-dependent inter-cellular transfer of membrane fragments and associated molecules from antigen presenting cells to effector lymphocytes. We previously demonstrated that trogocytosis also occurs between tumor target and cognate melanoma antigen-specific cytotoxic T cells (CTL). Here we show that, following trogocytosis, immune effector cells acquire molecular components of the tumor, including surface antigens, which are detectable by specific monoclonal antibodies. We demonstrate that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…The Jacobson and Lotem groups demonstrated that trogocytosis could be used to detect and isolate antigen-specific CTLs via either transfer of pMHC complexes (Tomaru et al, 2003), membrane (Machlenkin et al, 2008), or surface antigens (Eisenberg et al, 2013). Using trogocytosis and signaling analysis, the Lotem group also demonstrated that a peptide-specific (MART26-35) TIL response consisted of individual T cells with different functional responses (Uzana et al, 2012), consistent with our previous findings that only high avidity TAA-specific T cells could kill tumor cells (Stuge et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The Jacobson and Lotem groups demonstrated that trogocytosis could be used to detect and isolate antigen-specific CTLs via either transfer of pMHC complexes (Tomaru et al, 2003), membrane (Machlenkin et al, 2008), or surface antigens (Eisenberg et al, 2013). Using trogocytosis and signaling analysis, the Lotem group also demonstrated that a peptide-specific (MART26-35) TIL response consisted of individual T cells with different functional responses (Uzana et al, 2012), consistent with our previous findings that only high avidity TAA-specific T cells could kill tumor cells (Stuge et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon is not exclusive to T cells, as B cells (16,17), NK cells (18)(19)(20), basophils (21), macrophages (22,23), neutrophils (24)(25)(26), and dendritic cells (27,28) have all been reported to perform trogocytosis. With elevated levels of trogocytosis documented in sites of autoimmune inflammation (29), viral and parasitic infections (30)(31)(32), rheumatoid arthritis (33), and tumor environments (34,35), this widely observed event has been proposed to play a role in the modulation of immune responses (27,(36)(37)(38)(39)(40)(41).…”
mentioning
confidence: 99%
“…Cytotoxic CD8 + T cells are considered to be the major player in cancer immunotherapy. The increased proportion of tumor-infiltrating T lymphocytes has been found to correlate with improved clinical outcome in several human cancers, such as ovarian cancer, melanoma, and prostate cancer (48)(49)(50). We further demonstrated that the antitumor immunity conferred by the tumor cells modified with LX/(IL-7) was associated with the enhancement of CD8 + T cell functions.…”
Section: Discussionmentioning
confidence: 58%